Copepod community along the Mediterranean coast of Morocco (Southwestern Alboran Sea) during spring - BERRAHO, A.; ABDELOUAHAB, H.; CHARIB, S.; ESSARRAJ, S.; LARISSI, J.; ABDELLAOUI, B.; CHRISTOU, E. D. (Mediterranean Marine Science, 2016)
Copepod community along the Mediterranean Moroccan coast was investigated, for the first time, during April 2013. Total abundance varied from 53 to 4557 ind. m-3 and high values were found in coastal waters. Oithona nana and Paracalanus parvus dominated in the entire area and species diversity was decreasing from the West to the East. Hierarchical clustering revealed three groups of stations, depending on their geographic position (western, central and eastern areas). Indicator species analysis pointed out that Clausocalanus furcatus and Gaetanus sp. were significantly associated with Group I, Clausocalanus sp., Centropages sp. and Centropages chierchiae with Group II, whereas Temora longicornis was significantly associated with Group III. Detrended Correspondence Analysis based on the species abundance and environmental variables (temperature, salinity, chlorophyll-a), highlighted a more or less similar setting of stations which was related to salinity and temperature. The presence of three anticyclonic gyres at the northern part of the study area is suggested as the major factor acting on the variability of copepod community along the Mediterranean Moroccan coast.